Dismantling Reified African Culture Through Localised Homosexualities In Uganda - Nyanzi, Stella (Culture, health & sexuality, 2013)
Uganda's Anti-Homosexuality Bill of 2009 aimed at protecting the cherished culture of the people against emergent threats to the traditional heterosexual family. The Bill's justification, however, lay in myopic imaginings of a homogenous African-ness and pedestrian oblivion to pluralities within African sexualities. This paper revisits the debate that homosexuality is ‘un-African’. Rhetoric analysis of the Anti-Homosexuality Bill exposes how dominant discourses of law, medicine, religion, geography and culture reinforce the view that homosexuality is foreign to Africa. Based on ethnography in contemporary Uganda, I explore how self-identified same-sex-loving individuals simultaneously claim their African-ness and their homosexuality. Their strategies include ethnic belonging, membership to kinship structures, making connections with pre-colonial histories of homosexuality, civic participation in democratic processes, national identity, organising of lesbian, gay, bisexual, transgender, intersex and questioning support groups, language and nomenclature, visibility and voice in local communal activities, solidarity and adherence to cultural rituals. In present-day Uganda, same-sex-loving men, women and transgender people variously assert their African-ness.
Keywords: African culture; homosexuality; ethnography; culture; Uganda